Keragaan Sifat Galur F5 Kedelai Hasil Seleksi F3 Persilangan Grobogan dengan KM 25 - Sahnel Govindo Papahan; Aslim Rasyad (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
The objective of this research was to determine the F5 lines performance of soybean obtained after selection of F3 generatian from Grobogan x KM 25 cross. The study was conducted at the Experiment station Fakulty of Agriculture The University of Riau Pekanbaru.  The field experiment was established from  April 2019 to July 2019 and assigned by a randomized block design. Thirteen genotypes consisting of 11 F5 lines from Grobogan x KM25 cross and the two parents lines were grown in a plot of 200 cm x 120 cm with planting space of 40 cm x 40 cm. The results indicated that several F5 lines performed differently in some traits to their parents lines. The characters included plant height, flowering date, days to harvest, number of filled pods, grain weight per plant, grain yield per m2, and harvest index. There were three F5 lines had taller stem, one  line having late flowering date, and three lines that faster days to harvest than their parents. In term of yield components, three lines beared more filled pods,  one line yielded heavier grain weight per plant, and two lines had greater grain weight per m2 compared to their parents. There were two lines with greater harvest index than the two parents.  Further implication of the results was the potential lines are GK25-3-9, GK25-3-12, GK25-3-18, GK25-3-20, GK25-3-22, and GK25-3-37. Keywords:Performance, F5 Soybean Line, yield component